The role of the vuca method in understanding the phenomenon of fomo and doom spending among the younger generation - Handani, Sari Sri; Anggraeni, Iseu; Sofwan, Syifa Vidya; Mustika, Dena (Panicgogy International Journal, 2024)
Dynamic changes in the digital era create great challenges for the younger generation, especially in an environment characterized by Volatility, Uncertainty, Complexity, and Ambiguity (VUCA). Fear of Missing Out (FOMO) and doom spending is a significant behavioral manifestation among the younger generation, including Bale Bandung University students. This study aims to analyze the role of the VUCA framework in shaping both phenomena and provide insight into the factors that influence these behaviors. The research method used was a Systematic Literature Review (SLR), which allows for a structured analysis of relevant academic literature. Data was obtained from reputable journals, conference proceedings, and educational books using strict inclusion and exclusion criteria. Data analysis was conducted by categorizing the findings based on the elements of VUCA and its relationship with FOMO and doom spending. Translated with DeepL.com (free version)The results show that VUCA elements, such as uncertainty and complexity, exacerbate FOMO and doom spending tendencies, especially through the influence of social media (3 article). College students who face social and financial pressures in a dynamic environment exhibit impulsive consumptive behavior as a coping mechanism for these pressures. The findings are consistent with previous studies, but extend the literature by integrating the VUCA framework in the analysis. This research makes a significant contribution to understanding the impact of VUCA on young people's social behavior and opens opportunities for the development of intervention strategies. These results are relevant for educational institutions and policymakers in designing digital literacy, financial management, and mental support programs. In conclusion, a VUCA-based approach can be a foundation for addressing increasingly complex social challenges in the digital age.